Rare functional variants in genome–wide association identified candidate genes for nonsyndromic clefts in the African population. Issue 10 (31st July 2014) - Butali, Azeez; Mossey, Peter; Adeyemo, Wasiu; Eshete, Mekonen; Gaines, Lauren; Braimah, Ramat; Aregbesola, Babatunde; Rigdon, Jennifer; Emeka, Christian; Olutayo, James; Ogunlewe, Olugbenga; Ladeinde, Akinola; et al.
Abstract Nonsyndromic clefts of the lip and palate (NSCLP) are complex genetic traits. Together, they are classified as one of the most common birth defects with a prevalence of 1/700 live births. Genome‐wide association studies (GWAS) for nonsyndromic cleft lip with or without cleft palate (NSCL[P]) revealed significant association for common single nucleotide polymorphisms near genes involved in craniofacial development i.e., MAFB, PAX7, VAX1, ARHGAP29 (ABCA4 locus), and IRF6. Sequencing of protein coding regions of the NSCL(P) GWAS candidate genes or adjacent genes suggest a role for rare functional variants. Replication studies in the African population did not observe any significant association with the GWAS candidate genes. On the other hand, the role of rare functional variants in GWAS candidate genes has not been evaluated in the African population. We obtained saliva samples from case triads in Nigeria and Ethiopia for Sanger sequencing of the GWAS candidate genes (MAFB, PAX7, VAX1, ARHGAP29, and IRF6) in order to identify rare functional variants. A total of 220 African samples (140 Nigerians and 80 Ethiopians) were sequenced and we found the following new rare variants— p.His165Asn in the MAFB gene, p.Asp428Asn in the PAX7, a splice‐site variant that creates a new donor splice‐site in PAX7. We also found three previously reported missense variants p.Gly466Ser in PAX7; p.Leu913Ser and Arg955His in ARHGAP29. No de novo mutations were found. Future genome‐wide association and sequencing studies should be conducted using samples from Africa in order to identify new molecular genetic factors that contribute to the etiology of NSCLP. © 2014 Wiley Periodicals, Inc.